Relationship between Bengaluru City Undergraduate Students’ Oral Health Literacy and Oral Health Status - Rajkumari Surbala Devi; Manish Kumar; Subodh Kumar; Rejita Nongmeikapam; B Rahul (Journal of Pharmacy and Bioallied Sciences, 2025)
Background: Poor oral health outcomes and underutilization of oral care services might result from low oral health literacy (OHL). It’s critical to identify individuals with insufficient OHL and enhance provider–patient communication. The purpose of this research was to ascertain if OHL and oral health conditions among Bengaluru city undergraduate students were related. Materials and Methods: To measure OHL, 1600 undergraduate students in Bengaluru City participated in a cross-sectional research using the Rapid Estimate of Adult Literacy in Dentistry-30 (REALD-30). After the questionnaire was administered using the WHO Oral Health Assessment Form-2013, an oral examination was conducted. Correlation and comparison tests were included of the statistical analysis, and P < 0.05 was considered significant. Results: OHL and dental status were shown to be negatively correlated. Gingival bleeding, periodontal pockets, loss of attachment, tooth erosion, and trauma all showed significant variations in OHL (P < 0.001). There was no discernible correlation with enamel fluorosis (P = 0.14). OHL scores were higher for students who did not need therapy than for those who did (P < 0.001). Conclusion: Poorer oral health condition is linked to lower OHL. People who are at risk for poor oral health outcomes may be identified with the use of OHL assessment tools.